RESEARCH ON CUTTING VIBRATION OF HIGH SPEED MILLING HIGH HARDNESS HARDENED STEEL WITH COATED TOOLS - XIE YingXing; WANG ChengYong (Jixie qiangdu)
High speed milling of high hardness hardened steel has the characteristics of high cutting speed and high machining surface hardness,smooth and efficient milling can ensure quality and accuracy,while the generation of cutting vibrations limits the superiority of hard cutting technology. By designing high speed milling of high hardness（ HRC 48 ～ 68）hardened steel under different technological parameters,the cutting vibration signal was collected by LMS Test 9 A experiment analysis software,and the time and frequency domain analyses were analyzed,the relationships among the cutting vibration,the hardness and cutting technological parameters of the hardened steel were studied. The results showed that when the hardness of hardened steel increased,the friction between the rake face of the coated tool and the hardened steel increased,the friction resistance in the feed direction increased,and the amplitude of the vibration signal increased; the vibration signals generated by Ti Al N and Al Cr N coated tools were smaller than those of Ti Si N and Cr Si N coated tools; the addition of Al element in the coating design has a positive effect on suppressing and reducing cutting vibration of hardened steel; the changes of cutting parameters had different effects on the cutting vibration in the feed direction of the cutting tool; in order to obtain a lower cutting vibration amplitude and higher cutting efficiency,the cutting parameter value should be selected in preference to minimize cutting vibration.